Argo Float Reveals Biogeochemical Characteristics Along the Freshwater Gradient Off Western Patagonia - Galán, Alexander; Saldías, Gonzalo S.; Corredor-Acosta, Andrea; Muñoz, Richard; Lara, Carlos; Iriarte, José Luis (Frontiers in Marine Science, 2021)
The coastal region off Chilean Patagonia has been poorly studied due to the lack of available observations. Here we analyzed, by the very first time, biogeochemical (BGC) data to elucidate the role that biological and physical processes play on nitrate, oxygen, pH and hydrographic variables, along a salinity gradient off central Patagonia. Argo float profiles covering the upper ocean from December 2015 to July 2019 reveal that offshore waters are characterized by low temperatures and high salinities related to high oxygen and medium-high values of pH and nitrate. As the Argo float drifted onshore, freshwater influences the upper 50–100 m with low salinity and high temperature. Waters under the influence of the continental runoff were characterized by medium-to-high oxygen and pH levels, and the lowest nitrate concentrations. Interestingly, oxygen-deficient waters located beneath the freshwater-modified layer showed the lowest pH and highest nitrate. A comprehensive analysis of the temporal and vertical variability of the oxygen:nitrate ratio, in conjunction with biological-related and physical parameters, indicates that the BGC variability seems to be the result of a synergistic interaction between physical and biological processes, where the stratification sets up the environment and promotes the biological response that, in turn, is auto-regulated by modifying the chemical composition in the freshwater-influenced zone. The arrival of future floats with additional sensors (Chlorophyll/Fluorescence, Photosynthetically Active Radiation, Backscatter, etc.) will add new BGC properties that improve our understanding of the coastal marine response to the increasing freshwater input off western Patagonia in the context of climate change.